SISTEM PENDUKUNG KEPUTUSAN PENENTUAN RANKING SMK TERBAIK DI LAMPUNG TENGAH MENGGUNAKAN METODE MULTIPLE ATTRIBUTE DECISION MAKING - Sri Ipnuwati; Dian Puspita; Ria Rukmana (Jurnal TAM (Technology Acceptance Model), 2019)
Determining the right and best school is not easy. We must look for information in the schools that we go to, then compare it and choose which schools are suitable according to the criteria, such as determining which Vocational School in Central Lampung we must determine from different aspects as consideration for reviewing the best Vocational Schools, therefore we use decision support system as the best method of determining Vocational School, Decision Support System is a computer-based interactive system that is able to help decision makers to find the best alternative based on predetermined criteria using the MADM method (Multiple Attribute Decision Making). This method was chosen because it is able to select the best alternative from a number of alternatives, in this case the intended alternative is to determine the best Vocational High School based on the specified criteria. The study was conducted by looking for weight values for each attribute. Of the five alternatives that are used as the highest sample values there are in the first alternative A1 with a value of 86 that indicates that alternative one is an alternative chosen as the best Vocational School in Central Lampung.